Brexit: Surname Diversity and Voting Patterns. Issue 4 (1st August 2016) - Borja, Mario Cortina; Stander, Julian; Valle, Luciana Dalla
Abstract: Mario Cortina Borja, Julian Stander and Luciana Dalla Valle examine associations between the results of the EU referendum and the prevalence of unique surnames across the UK Mario Cortina Borja, Julian Stander and Luciana Dalla Valle examine associations between the results of the EU referendum and surname diversity